Knowledge Management In Islamic Banking: The Role Of Organizational Culture, Technology, Motivation, Knowledge Assets, And Religiosity - Marlinda, Marlinda; Ilyas, Fithriady; Syahputra, Hendra (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2025)
This study was motivated by the challenges of knowledge management in the context of the transformation of conventional banking to Islamic banking in Aceh Province, in line with the implementation of the Qanun Lembaga Keuangan Syariah (Qanun LKS) or Islamic Financial Institutions Regulation. The purpose of this study is to analyze the influence of organizational culture, technology, motivation, and knowledge assets on the knowledge management of state-owned and regionally-owned bank employees in Banda Aceh, as well as to examine the role of religiosity as a moderating variable. The research data came from primary sources obtained from questionnaires distributed to 163 employees of Bank Syariah Indonesia (BSI), Bank Tabungan Negara Syariah (BTNS), and Bank Aceh Syariah (BAS). The results showed that technology and motivation had a significant positive effect, while organizational culture, knowledge assets, and religiosity had no effect, and religiosity did not moderate the relationship between variables. These findings indicate that improving the quality of knowledge management can be achieved through investment in information technology systems, optimization of knowledge sharing processes, and strengthening employee motivation, while ensuring that its implementation is in line with Islamic values and work ethics. This study suggests that Islamic banks in Aceh should strengthen internal training, develop knowledge documentation systems, and create a work environment that supports knowledge sharing.